The first record of Bergamina lineolata (Chydoridae; Aloninae) from Colombia - Fuentes-Reinés,J. M. (2023)
Abstract The Neotropical freshwater cladoceran Bergamina lineolata (Sars, 1901) was found in a small temporal pond in the Magdalena department. Hitherto, it has been reported in Brazil and El Salvador. It was originally described as Alonella lineolata by Sars, 1901 from Brazil and then placed to the genus Bergamina by Elmoor-Loureiro et al. (2013). This is the first record of this species in Colombia. B. lineolata can be identified by a unique combination of characters including: 1) a remarkably large and oblong postabdomen, with three denticles on distal corner; 2) basal spine of the claw very short, length less than the half claw diameter at base; 3) IDL with two setae shorter than ODL seta, armed with fine setules unilaterally in terminal half; 4) endite 1 of trunk limb I with a long smooth seta between endites 1 and 2.